ANTHROPOCENE AND ECOLOGICAL CONCERNS: A COMPARATIVE ANALYSIS OF NOVEL AND FILM DUNE - Dahiya, Yash; Chhikara, Mayur (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The paper discusses about Dune by Frank Herbert and its film adaptation as an ecological story of Arrakis. Rather than viewing Arrakis as an unusual environment to be used as a political conflict, the article understands the desert planet as a living system that determines scarcity, violence, and biological complexity that influence social and imperial institutions built over it. Along with ecocriticism, posthumanism, and film theory, the article claims that Dune does not just show ecology as a setting but acts as a fundamental framework of narrative. The functions of power, survival of life, all come together with climate, water, sandworms, and spice. Throughout the novel, Herbert repeatedly demonstrates that environmental knowledge is related to political consequences, so that understanding of the planet is necessary to survive. The same ecological logic is presented with visualization in film through broad desert landscapes, the exposed settlements, suspended harvesting machines, and the emergence of sandworm, which repetitively demonstrates the frailty of human technology. This article will argue that Dune provides one of the most effective approaches to thinking about the Anthropocene by reading the novel and film together. Arrakis turns into a speculative reflection about contemporary extractive systems. It may be regarded as an imperial order that requires dependence on resources that it lacks the ability to generate itself and an ecology that lacks complete control. The contrast of imperial exploitation and Fremen adaptation further explains the environmental politics of the text. It implies that it is not those who attempt to dominate the planet that will survive, but those who learn to know its limits and adapt to its needs. Dune thus comes out not only as a science-fiction epic, but also as a warning on planetary life, and challenges readers and viewers to reconsider how human ambition interacts with ecological systems that sustain life.